Pengaruh Investment Opportunity Set (IOS), dan pertumbuhan laba Terhadap Kualitas Laba Pada Perusahaan Real Estate dan Property yang terdapat di Bursa Efek Indonesia - Barus, Silvia Mileniati; Wijaya, Muslim (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the effect of Investment Opportunity Set (IOS) and Earnings Growth (PL) on Earnings Quality (KL) in Real Estate & Property sector companies listed on the Indonesia Stock Exchange. The sample used was 33 companies with data for three years. The analysis method used is multiple linear regression, with various classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The normality test results show that the data is normally distributed. The multicollinearity test shows that there is no strong relationship between the independent variables. The heteroscedasticity test shows that there is no particular pattern in the distribution of residuals. The autocorrelation test results also show the absence of autocorrelation symptoms in the model. However, the coefficient of determination test results show that IOS and PL only explain 8.6% of the variation in earnings quality. The F test shows that the regression model is not simultaneously significant, and the t test shows that neither IOS nor PL has a partially significant effect on Earnings Quality. Thus, it can be concluded that IOS and Earnings Growth do not have a significant influence on Earnings Quality in the companies studied.